2023
DOI: 10.3389/fimmu.2023.1288517
|View full text |Cite
|
Sign up to set email alerts
|

Exploring causal relationships between inflammatory cytokines and allergic rhinitis, chronic rhinosinusitis, and nasal polyps: a Mendelian randomization study

Li Li,
Yuanding Zhang,
Hong Liu
et al.

Abstract: ObjectivesPrevious research has suggested connections between specific inflammatory cytokines and nasal conditions, including Allergic Rhinitis (AR), Chronic Rhinosinusitis (CRS), and Nasal Polyps (NP). However, a lack of robust research establishing the causal underpinnings of them. This Mendelian Randomization (MR) study aims to evaluate the causal relationships between 41 inflammatory cytokines and the incidence of AR, CRS and NP.MethodsThis study employed a two-sample MR design, harnessing genetic variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Using the example of patients with Sjögren's disease, it was shown that HMGB1, together with TNF-α and IL-1β, can form a pro-inflammatory loop that contributes to chronic inflammation of the nasal mucosa and paranasal sinuses [38]. A positive correlation was also shown between increased levels of circulating TNF-α and an increased risk of developing allergic rhinitis (OR = 1.01478, 95% CI = 1.00225-1.02746, p = 0.02067), that is, the presence of a cause-and-effect relationship [39]. These results are consistent with our findings.…”
Section: Discussionmentioning
confidence: 97%
“…Using the example of patients with Sjögren's disease, it was shown that HMGB1, together with TNF-α and IL-1β, can form a pro-inflammatory loop that contributes to chronic inflammation of the nasal mucosa and paranasal sinuses [38]. A positive correlation was also shown between increased levels of circulating TNF-α and an increased risk of developing allergic rhinitis (OR = 1.01478, 95% CI = 1.00225-1.02746, p = 0.02067), that is, the presence of a cause-and-effect relationship [39]. These results are consistent with our findings.…”
Section: Discussionmentioning
confidence: 97%